2019
DOI: 10.1136/emermed-2019-208409
|View full text |Cite
|
Sign up to set email alerts
|

Framing of clinical information affects physicians’ diagnostic accuracy

Abstract: BackgroundFraming bias occurs when people make a decision based on the way the information is presented, as opposed to just on the facts themselves. How the diagnostician sees a problem may be strongly influenced by the way it is framed. Does framing bias result in clinically meaningful diagnostic error?MethodsWe created three hypothetical cases and asked consultants and registrars in Emergency Medicine and Internal Medicine to provide their differential diagnoses and investigations list. Two of the presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The respondents gave answers ranging from 10% to 90%, despite receiving identical information at the start . This can lead to an undesired variety of testing rates as well as clinical outcomes …”
Section: Discussionmentioning
confidence: 99%
“…The respondents gave answers ranging from 10% to 90%, despite receiving identical information at the start . This can lead to an undesired variety of testing rates as well as clinical outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Studies aiming to discern the impact of cognitive behaviour such as confidence, heuristics, knowledge, skills or uncertainty or contextual factors such as practices or patient behaviour, predominantly operationalized CDM as dispositional decisions or cognitive processes. Regardless of the operationalization, the vast majority of studies [41,[69][70][71][72][73][74][75][76][77][78] found that clinician cognition or contextual factors negatively affected CDM performance or the accuracy of diagnostics. Only two [79,80] found that CDM performance was unaffected by cognitive factors, however still arguing that this might not be true with more complex diseases [79].…”
Section: Effects Of Cognitive Processes or Contextual Factorsmentioning
confidence: 99%
“…Of these thirteen publications, all but two [43,78] operationalized CDM as cognition, describing the process itself and influencing factors. CDM was defined as a 'mental process' [21,69,82] referring to thought…”
Section: Cdm In Gem As a Phenomenonmentioning
confidence: 99%
“…Studies aiming to discern the impact of cognitive behaviour or contextual factors, predominantly operationalized CDM as dispositional decisions or cognitive processes. Regardless of the operationalization, the vast majority of studies (42,(70)(71)(72)(73)(74)(75)(76)(77)(78)(79) found that clinician cognition (i.e. con dence or heuristics) or contextual factors (i.e.…”
Section: Effects Of Cognitive Processes or Contextual Factorsmentioning
confidence: 99%
“…The included publications also linked increased error-risk to age-speci c biases or overreliance on heuristics (70,79,80,84). Here, speci cally the complexity of elderly patients were described to cause errors as normal clinical practice is guided by heuristics, which run the risk of simplifying complexity in urgent clinical settings (22).…”
Section: : Biases and Heuristicsmentioning
confidence: 99%